Experimental Test of Single Cylinder Otto Engine Performance on Dynotest Chassis Using Premium Fuel Types, Pertalite and Pertamax - Agung Mulia Pulungan (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Public vehicles such as motorcycles today could use some types of fuel selection from PT. Pertamina for premium gasoline engines among other things, pertalite and pertamax. Each type of fuel has an octane number of different. Engine performance is heavily influenced by several factors, including the type of fuel used and the pistons (large and small combustion chamber volume). The purpose of this study was to determine the effect of different octane number of gasoline on the performance of torque, power, and then analyze the specific fuel consumption, brake thermal efficiency and exhaust emissions at otto engine. The results of the experimental test engine performance otto one cylinder indicates a maximum torque of 40 Nm at engine speed 1410 rpm when using gasoline pertamax, followed torque of 38 Nm at engine speed 1221 rpm when using gasoline pertalite and torque of 29 Nm at rpm 1877 when using premium gasoline. While the maximum power when using gasoline pertamax of 13,870 kW at 4409 rpm, followed pertalite 12,602 kW at 4041 rpm rotation, and premium gasoline amounted to 12,229 kW at 4688 rpm rotation. For specific fuel consumption is minimal (economical) when using gasoline pertamax amounted to 0.171 kg/kW.h at 4409 rpm, followed by gasoline pertalite of 0.229 kg/kW.h at 4041 rpm, then premium gasoline amounted to 0.273 kg/kW. h on 4688 rpm. Brake thermal efficiency (BTE) is achieved when the maximum engine using gasoline pertamax amounted to 48.124% at engine speed 4409 rpm, followed by the gasoline engine BTE pertalite 36.659% at 4041 rpm and the engine BTE premium gasoline amounted to 31.673% at 4688 rpm.